# Question

Hi, I would need some help with this along with an explanation. I am rather reluctant in simply adding the spent with the remainder. Please help me on this, thank you in advance

Source: Anglo-Chinese School Junior

Highly appreciate if explained thank you

0 Replies 0 Likes ✔Accepted Answer

J      K

Starting      1         1

Spending   3u     2u

Left             5v       8v

3u + 5v = 2u + 8v

3u – 2u = 8v – 5v

u = 3v

5v : 3u = 5v : 3(3v) = 5v : 9v = 5 : 9

Thank you, but can you explain your workings and why you did so, I would highly appreciate if you do so 😀

3 Replies 0 Likes

Highly appreciate if explained thank you

0 Replies 0 Likes

The two boys have same amount of money at first.

Jason spent 3u, Keming 2u

Jason left 5v, Keming 8v

So 3u+5v = 2u+8v

Because amt spent and amt left added up to the original amt.

Jasom spent more than Keming. So 3u-2v

Keming’s left over will be more than Jason. So 8v-5u

Since they started with same amt of money, the difference in the spending will be equal to the different in left over amt. So,

3u-2v =  8v-5u